Slow Fluid Leakage along Faults: A Multidisciplinary Study on the Mud Volcanoes of the Bolle della Malvizza (Southern Apennines, Italy) - Stefano Vitale; Stefano Albanese; Maurizio Ambrosino; Pietro Boni; Domenico Cicchella; Claudio De Paola; Maria Giulia Di Giuseppe; Carmela Fabozzi; Roberto Isaia; Jacopo Natale; Mubashir Mehmood; Fabio Pagliara; et al. (Journal of Earth Science, 2026)

Geology, fluid inclusions, sulfur isotopes, and Rare Earth Element signatures of the Ain Mimoun barite vein-type ore-deposit, Northeastern Algeria - Imene Benhammoud; Abdelhak Boutaleb; Omar Haddouche; Maria Boni; Nicola Mondillo (Journal of African Earth Sciences, 2025)

Vanadium and other critical elements in North Gondwana Silurian black shales: The SE Sardinia (Italy) case - Maria Boni; Nicola Mondillo; Licia Santoro; Giuseppina Balassone (Journal of Geochemical Exploration, 2025)

Congenital goiter in an alpaca (Vicugna pacos) fetus concomitant with brain pathology in the dam: composing the puzzle - Letizia Tomassini; Maria Teresa Mandara; Piero Boni; Elisabetta Manuali; Benedetta Sensini; Domenico Caivano; Elvio Lepri (Veterinary Research Communications, 2025)

Genetic variants and phenotypic data curated for the CAGI6 intellectual disability panel challenge - Maria Cristina Aspromonte; Alessio Del Conte; Roberta Polli; Demetrio Baldo; Francesco Benedicenti; Elisa Bettella; Stefania Bigoni; Stefania Boni; Claudia Ciaccio; Stefano D’Arrigo; Ilaria Donati; Elisa Granocchio; et al. (Human Genetics, 2025)
Neurodevelopmental disorders (NDDs) are common conditions including clinically diverse and genetically heterogeneous diseases, such as intellectual disability, autism spectrum disorders, and epilepsy. The intricate genetic underpinnings of NDDs pose a formidable challenge, given their multifaceted genetic architecture and heterogeneous clinical presentations. This work delves into the intricate interplay between genetic variants and phenotypic manifestations in neurodevelopmental disorders, presenting a dataset curated for the Critical Assessment of Genome Interpretation (CAGI6) ID Panel Challenge. The CAGI6 competition serves as a platform for evaluating the efficacy of computational methods in predicting phenotypic outcomes from genetic data. In this study, a targeted gene panel sequencing has been used to investigate the genetic causes of NDDs in a cohort of 415 paediatric patients. We identified 60 pathogenic and 49 likely pathogenic variants in 102 individuals that accounted for 25% of NDD cases in the cohort. The most mutated genes were ANKRD11, MECP2, ARID1B, ASH1L, CHD8, KDM5C, MED12 and PTCHD 1 The majority of pathogenic variants were de novo, with some inherited from mildly affected parents. Loss-of-function variants were the most common type of pathogenic variant. In silico analysis tools were used to assess the potential impact of variants on splicing and structural/functional effects of missense variants. The study highlights the challenges in variant interpretation especially in cases with atypical phenotypic manifestations. Overall, this study provides valuable insights into the genetic causes of NDDs and emphasises the importance of understanding the underlying genetic factors for accurate diagnosis, and intervention development in neurodevelopmental conditions.

Are we ready for the application of the EU Regulation on wastewater reuse in agriculture? A techno-economic preliminary evaluation based on a case-study - Camilla Di Marcantonio; Francesca Mangiagli; Maria Rosaria Boni; Jessica Bartolucci; Simona Bongirolami; Roberto Romano; Andrea Martelli; Davide Rapinesi; Filiberto Altobelli; Agostina Chiavola (Journal of Environmental Management, 2025)

Peripheral blood mononuclear cell bioenergetics and skeletal muscle mitochondrial function in individuals with and without type 2 diabetes - Philipp Harbecke; Finn-Marten Büscher; Marie Therese Schmitz; Eva Maria Elmenhorst; Laura de Boni; Petra Frings-Meuthen; Jens Jordan; Jörn Rittweger; Dominik Pesta (Biochimica et Biophysica Acta (BBA) - Bioenergetics, 2024)

A critical analysis on the limits and possibilities of the μ-Raman as a routine method for microplastics determination in drinking water - Margherita Barchiesi; Camilla Di Marcantonio; Alessandro Frugis; Marco Lazzazzara; Valentina Gioia; Mario Castellani; Maria Rosaria Boni; Agostina Chiavola (Journal of Water Process Engineering, 2024)

Ag and Pb isotope systematics in galena ores from southern Sardinia and southern France flag potential silver sources in antiquity - Francis Albarede; Maria Boni; Janne Blichert-Toft; Markos Vaxevanopoulos; Katrin Westner; Jean Milot; Marine Pinto; Philippe Télouk (Archaeological and Anthropological Sciences, 2024)
While lead isotopes serve to determine potential ore provenance, silver isotopes help evaluate if a specific ore flagged by Pb isotopes has actually been exploited as a silver source of bullion in antiquity. The combination of Ag and Pb isotopes thus constitutes a powerful tool to address provenance and identify potential ore sources. It has recently been observed that the vast majority of silver isotopic abundances in hundreds of silver coins from different historical periods (pre-Roman and Roman, Middle Ages, early modern times) and different localities (Persia, Greece, Rome, Western Europe, England, Spanish Americas) falls in a remarkably narrow interval (± 0.1 permil, or ± 1 on the epsilon scale used by geochemists to enhance the visibility of small isotopic differences, group 1). Five Greek coins and some pieces from Levantine hacksilber hoards dated to the Late Bronze and Early Iron Ages have isotopic abundances somewhat below the range of group 1 (–0.2 to –0.1 permil, or -2 to -1 on the epsilon scale, group 2). The coverage of Ag isotopes in ores from the western Mediterranean, with the exception of Iberia, is inexistant. Here the above-mentioned approach is illustrated with new Pb and Ag isotopic analyses of samples from southern Sardinia and southern France. The majority of Ag isotope compositions of galena samples from Sardinia belongs to group 2 and none to group 1. While scholarly works imply that Sardinia may have provided silver to the Levant during the Iron Age, the exact location of the Sardinian ores that contributed to classical and archaic Greek coins is still unknown. Galena samples from southern France (the Pyrenees, Montagne Noire, Cévennes) are characterized by Ag isotope compositions from both groups 1 and 2, indicating that silver-bearing ore deposits in Gaul could be considered a potential source for silver bullion, both before and during the Roman era.

Photogrammetry scans for neuroanatomy education - a new multi-camera system: technical note - André S. B. Oliveira; Luciano C. P. C. Leonel; Megan M. J. Bauman; Alessandro De Bonis; Edward R. LaHood; Stephen Graepel; Michael J. Link; Carlos D. Pinheiro-Neto; Nirusha Lachman; Jonathan M. Morris; Maria Peris-Celda (Neuroinformatics, 2024)

Well-preserved fallout basaltic tuff in central Paraná-Etendeka Large Igneous Province: pyroclastic evidence of high fire-fountain eruptions - Marcell Leonard Besser; Otavio Augusto Boni Licht; Eleonora Maria Gouvêa Vasconcellos (Bulletin of Volcanology, 2023)

A sustainable approach to enhance heavy hydrocarbons removal in landfarming treatment - Camilla Di Marcantonio; Agostina Chiavola; Alessandra Noce; Elisabetta Straccamore; Andrea Giannuzzi; Jacopo Jirillo; Francesco Gallo; Maria Rosaria Boni (Biodegradation, 2023)
The present study aimed to evaluate the best strategy to enhance the degradation rate of heavy petroleum hydrocarbons (HPH) contaminated soil in a landfarming plant. Samples of real contaminated soil, further spiked with HPH, were treated in mesocosm reactors simulating the landfarming system. One reactor was operated without any modification compared to the real landfarming plant. The other three reactors were operated with different strategies to improve the removal rate: biostimulation (BS) through the addition of nitrogen and phosphorus; bioaugmentation (BA) with the inoculation of sludge produced in the treatment of the process water from the oil re-fining plant of the same industrial area; combination of biostimulation and bioaugmentation (BAS). The biostimulation (BS) was the most effective strategy, leading to a reduction of the remediation time by 35% as compared to the traditional treatment. Bioaugmentation (BA) also provided positive effects leading to a reduction of the remediation time by 24%; its performance improved further when the addition of sludge was combined with the increase of phosphorous (BAS). Therefore, the key tool was represented by the phosphorous availability, whereas the application of sludge was most useful to provide waste with a new possibility of reuse, thus fulfilling the principles of the circular economy. The final characterization showed that the treated soil was suitable for reuse in industrial areas according to the legislation in force.

Unexpected finding of a rare pathogenic germline BRCA1 variant in an intrahepatic cholangiocarcinoma using the Oncomine Focus DNA assay: clinical and diagnostic implications - Maria De Bonis; Francesco Mannavola; Lisa Salvatore; Elisa De Paolis; Camilla Nero; Luciano Giacò; Giampaolo Tortora; Felice Giuliante; Andrea Urbani; Giovanni Scambia; Nicola Normanno; Angelo Minucci (Molecular Biology Reports, 2023)

Hydrovolcanic eruptions of the Paraná Igneous Province: Insights from mafic volcaniclastic deposits in Sertanópolis, Paraná, Brazil - Lucas Albanese Valore; Otavio Augusto Boni Licht; Eleonora Maria Gouvea Vasconcellos; Bruno Guimarães Titon (Journal of Volcanology and Geothermal Research, 2023)

A step forward on site-specific environmental risk assessment and insight into the main influencing factors of CECs removal from wastewater - Camilla Di Marcantonio; Agostina Chiavola; Valentina Gioia; Simone Leoni; Giancarlo Cecchini; Alessandro Frugis; Claudia Ceci; Massimo Spizzirri; Maria Rosaria Boni (Journal of Environmental Management, 2023)

Behavioral alterations and gills damage in Mytilus galloprovincialis exposed to an environmental concentration of delorazepam - Chiara Fogliano; Rosa Carotenuto; Raffaele Panzuto; Valentina Spennato; Salvatore De Bonis; Palma Simoniello; Anja Raggio; Bice Avallone; Claudio Agnisola; Chiara Maria Motta (Environmental Toxicology and Pharmacology, 2023)

High P2X6 receptor expression in human bladder cancer predicts good survival prognosis - Fabrícia Dietrich; Angélica Regina Cappellari; Eduardo Cremonese Filippi-Chiela; Patrícia Boni de Paula; Julia Brandt de Souza; Stefano Walter Agatti; Roberta Andrejew; Rafael Roesler; Fernanda Bueno Morrone; Ana Maria Oliveira Battastini (Molecular and Cellular Biochemistry, 2022)

Duplex high resolution melting analysis (dHRMA) to detect two hot spot CYP24A1 pathogenic variants (PVs) associated to idiopathic infantile hypercalcemia (IIH) - Maria De Bonis; Elisa De Paolis; Maria Elisabetta Onori; Giorgia Mazzuccato; Antonio Gatto; Pietro Ferrara; Pietro Manuel Ferraro; Andrea Urbani; Angelo Minucci (Molecular Biology Reports, 2021)
Pathogenic variants (PVs) in CYP24A1 gene are associated with Idiopathic Infantile Hypercalcemia disease (IIH). The identification of CYP24A1 PVs can be a useful tool for the improvement of target therapeutic strategies. Aim of this study is to set up a rapid and inexpensive High Resolution Melting Analysis (HRMA)-based method for the simultaneous genotyping of two hot spot PVs in CYP24A1 gene, involved in IIH. A duplex-HRMA (dHRMA) was designed in order to detect simultaneously CYP24A1 c.428_430delAAG , p.(Glu143del) (rs777676129) and c.1186C > T , p.(Arg396Trp) (rs114368325), in peculiar cases addressed to our Laboratory. dHRMA was able to identify clearly and simultaneously both hot spot CYP24A1 PVs evaluating melting curve shape and melting temperature (T m ). This is the first dHRMA approach to rapidly screen the two most frequent CYP24A1 PVs in peculiar case, providing useful information for diagnosis and patient management in IIH disease.

Mineralogy, fluid inclusions, and sulfur isotope studies of Ghar Rouban Barite (Pb-Zn) deposit, Western Algeria - Nacera Hadj Mohamed; Abdelhak Boutaleb; Maria Boni; Djamel Eddine Aissa (Arabian Journal of Geosciences, 2021)

The BRCA1 c.788G > T (NM_007294.4) variant in a high grade serous ovarian cancer (HGSOC) patient: foods for thought - Elisa De Paolis; Antonella Pietragalla; Maria De Bonis; Anna Fagotti; Andrea Urbani; Giovanni Scambia; Angelo Minucci (Molecular Biology Reports, 2021)

Low levels of frailty in HIV-positive older adults on antiretroviral therapy in northern Tanzania - Clare Bristow; Grace George; Grace Hillsmith; Emma Rainey; Sarah Urasa; Sengua Koipapi; Aloyce Kisoli; Japhet Boni; Grace Anderson Saria; Sherika Ranasinghe; Marcella Joseph; William K. Gray; et al. (Journal of NeuroVirology, 2021)
There are over 3 million people in sub-Saharan Africa (SSA) aged 50 and over living with HIV. HIV and combined antiretroviral therapy (cART) exposure may accelerate the ageing in this population, and thus increase the prevalence of premature frailty. There is a paucity of data on the prevalence of frailty in an older HIV + population in SSA and screening and diagnostic tools to identify frailty in SSA. Patients aged ≥ 50 were recruited from a free Government HIV clinic in Tanzania. Frailty assessments were completed, using 3 diagnostic and screening tools: the Fried frailty phenotype (FFP), Clinical Frailty Scale (CFS) and Brief Frailty Instrument for Tanzania (B-FIT 2). The 145 patients recruited had a mean CD4 + of 494.84 cells/µL, 99.3% were receiving cART and 72.6% were virally suppressed. The prevalence of frailty by FFP was 2.758%. FFP frailty was significantly associated with female gender ( p = 0.006), marital status ( p = 0.007) and age ( p = 0.038). Weight loss was the most common FFP domain failure. The prevalence of frailty using the B-FIT 2 and the CFS was 0.68%. The B-FIT 2 correlated with BMI ( r = − 0.467, p = 0.0001) and CD4 count in females ( r = − 0.244, p = 0.02). There is an absence of frailty in this population, as compared to other clinical studies. This may be due to the high standard of HIV care at this Government clinic. Undernutrition may be an important contributor to frailty. It is unclear which tool is most accurate for detecting the prevalence of frailty in this setting as levels of correlation are low.

BRCA testing delay during the COVID-19 pandemic: How to act? - Angelo Minucci; Giovanni Scambia; Maria De Bonis; Elisa De Paolis; Concetta Santonocito; Anna Fagotti; Ettore Capoluongo; Paola Concolino; Andrea Urbani (Molecular Biology Reports, 2021)

Modulating chitosan-PLGA nanoparticle properties to design a co-delivery platform for glioblastoma therapy intended for nose-to-brain route - Natália N. Ferreira; Sara Granja; Fernanda I. Boni; Fabíola G. Prezotti; Leonardo M. B. Ferreira; Beatriz S. F. Cury; Rui M. Reis; Fátima Baltazar; Maria Palmira D. Gremião (Drug Delivery and Translational Research, 2020)

High resolution melting profiles (HRMPs) obtained by magnetic induction cycler (MIC) have been used to monitor the BRCA2 status highlighted by next generation tumor sequencing (NGTS): a combined approach in a diagnostic environment - Giorgia Mazzuccato; Maria De Bonis; Vittoria Carboni; Claudia Marchetti; Andrea Urbani; Giovanni Scambia; Ettore Capoluongo; Anna Fagotti; Angelo Minucci (Molecular Biology Reports, 2020)

From Alpine-type sulfides to nonsulfides in the Gorno Zn project (Bergamo, Italy) - Nicola Mondillo; Federica Lupone; Maria Boni; Michael Joachimski; Giuseppina Balassone; Marcello De Angelis; Simone Zanin; Fabio Granitzio (Mineralium Deposita, 2020)

A novel strategy for glioblastoma treatment combining alpha-cyano-4-hydroxycinnamic acid with cetuximab using nanotechnology-based delivery systems - Natália N. Ferreira; Sara Granja; Fernanda Isadora Boni; Leonardo M. B. Ferreira; Rui M. Reis; Fátima Baltazar; Maria Palmira D. Gremião (Drug Delivery and Translational Research, 2020)

Remediation of Lead-Contaminated Water by Virgin Coniferous Wood Biochar Adsorbent: Batch and Column Application - Maria Rosaria Boni; Agostina Chiavola; Simone Marzeddu (Water, Air, & Soil Pollution, 2020)

Spliceogenic analysis of BRCA1 c.439T>C (rs794727800) variant by High Resolution Melting Analysis - Angelo Minucci; Giorgia Mazzuccato; Marco D’Indinosante; Lucia Di Nardo; Paola Concolino; Maria De Bonis; Andrea Urbani; Giovanni Scambia; Anna Fagotti; Ettore Capoluongo (Molecular Biology Reports, 2020)

Organochlorine pesticides in feathers of three raptor species in southern Brazil - Gustavo Francisco Aver; Silvia Espín; Renata De Boni Dal Corno; Antonio Juan García-Fernández; Maria Virginia Petry (Environmental Science and Pollution Research, 2020)

Sperm Motility Impairment in Free Spawning Invertebrates Under Near-Future Level of Ocean Acidification: Uncovering the Mechanism - Maria Consiglia Esposito; Raffaele Boni; Alessia Cuccaro; Elisabetta Tosti; Alessandra Gallo (Frontiers in Marine Science, 2020)

Effects of low-dosage ozone pre-treatment on the anaerobic digestion of secondary and mixed sludge - Agostina Chiavola; Emilio D’Amato; Maria Rosaria Boni (Environmental Science and Pollution Research, 2019)

Exploring by whole exome sequencing patients with initial diagnosis of Rubinstein–Taybi syndrome: the interconnections of epigenetic machinery disorders - Gloria Negri; Pamela Magini; Donatella Milani; Milena Crippa; Elisa Biamino; Maria Piccione; Stefano Sotgiu; Chiara Perrìa; Giuseppina Vitiello; Marina Frontali; Antonella Boni; Elisabetta Di Fede; et al. (Human Genetics, 2019)

Fate of selected drugs in the wastewater treatment plants (WWTPs) for domestic sewage - Agostina Chiavola; Pierpaolo Tedesco; Maria Rosaria Boni (Environmental Science and Pollution Research, 2019)

Capillary electrophoresis as alternative method to detect tumor genetic mutations: the model built on the founder BRCA1 c.4964_4982del19 variant - Maria De Bonis; Angelo Minucci; Giovanni Luca Scaglione; Elisa De Paolis; Gianfranco Zannoni; Giovanni Scambia; Ettore Capoluongo (Familial Cancer, 2019)

A study through batch tests on the analytical determination and the fate and removal of methamphetamine in the biological treatment of domestic wastewater - Maria Rosaria Boni; Agostina Chiavola; Camilla Di Marcantonio; Silvia Sbaffoni; Stefano Biagioli; Giancarlo Cecchini; Alessandro Frugis (Environmental Science and Pollution Research, 2018)

Erratum to: Unglazed pottery from the masjed-i jom’e of Isfahan (Iran): technology and provenance - Alberto De Bonis; Maria D’Angelo; Vincenza Guarino; Serena Massa; Faribah Saiedi Anaraki; Bruno Genito; Vincenzo Morra (Archaeological and Anthropological Sciences, 2018)

Germanium enrichment in supergene settings: evidence from the Cristal nonsulfide Zn prospect, Bongará district, northern Peru - Nicola Mondillo; Giuseppe Arfè; Richard Herrington; Maria Boni; Clara Wilkinson; Angela Mormone (Mineralium Deposita, 2018)

Unglazed pottery from the masjed-i jom’e of Isfahan (Iran): technology and provenance - Alberto De Bonis; Maria D’Angelo; Vincenza Guarino; Serena Massa; Faribah Saiedi Anaraki; Bruno Genito; Vincenzo Morra (Archaeological and Anthropological Sciences, 2017)

Fate of Some Endocrine Disruptors in Batch Experiments Using Activated and Inactivated Sludge - Agostina Chiavola; Pierpaolo Tedesco; Maria Rosaria Boni (Water, Air, & Soil Pollution, 2016)

Characterisation of protease activity in extracellular products secreted by Giardia duodenalis trophozoites treated with propolis - Érica Boarato David; Thaís Batista de Carvalho; Clarisse Maria Boni de Oliveira; Silvana Torossian Coradi; José Maurício Sforcin; Semíramis Guimarães (Natural Product Research, 2012)

Impact of Past Mining Activity on the Quality of Water and Soil in the High Moulouya Valley (Morocco) - Pietro Iavazzo; Daniela Ducci; Paola Adamo; Marco Trifuoggi; Antonello Migliozzi; Maria Boni (Water, Air, & Soil Pollution, 2012)

The carbonate-hosted willemite prospects of the Zambezi Metamorphic Belt (Zambia) - Maria Boni; Rosario Terracciano; Giuseppina Balassone; Sarah A. Gleeson; Alexander Matthews (Mineralium Deposita, 2011)

Nonsulfide zinc deposits in the Silesia–Cracow district, Southern Poland - Vito Coppola; Maria Boni; H. Albert Gilg; Bozena Strzelska-Smakowska (Mineralium Deposita, 2009)

Hypogene Zn carbonate ores in the Angouran deposit, NW Iran - Maria Boni; H. Albert Gilg; Giuseppina Balassone; Jens Schneider; Cameron R. Allen; Farid Moore (Mineralium Deposita, 2007)

Marble-hosted sulfide ores in the Angouran Zn-(Pb–Ag) deposit, NW Iran: interaction of sedimentary brines with a metamorphic core complex - H. Albert Gilg; Maria Boni; Giuseppina Balassone; Cameron R. Allen; David Banks; Farid Moore (Mineralium Deposita, 2006)

Influence of Stabilized-Dewatered Sludge Addition on Solid-Phase Clean-Up of a Soil Contaminated By Phenolic Compounds - Renato Baciocchi; Maria Rosaria Boni; Giusy Lombardi; Eugenia Porcelli (Water, Air, & Soil Pollution, 2003)

Characterization and Performance of Granular Iron as Reactive Media for TCE degradation by Permeable Reactive Barriers - Renato Baciocchi; Maria Rosaria Boni; Laura D'Aprile (Water, Air, & Soil Pollution, 2003)

Platform margins, microbial/serpulids bioconstructions and slope-to-basin sediments in the Upper Triassic of the ‘Verbicaro Unit’ (Lucania and Calabria, southern Italy) - Anna Climaco; Maria Boni; Alessandro Iannace; Valeria Zamparelli (Facies, 1997)